Rasch analysis of the Nottingham Extended Activities of Daily Living Scale - das Nair, Roshan; Moreton, Bryan; Lincoln, Nadina (Foundation for Rehabilitation Information, 2011)
Background and purpose: The Nottingham Extended Activities of Daily Living (EADL) Scale is frequently used in clinical practice and research in rehabilitation to assess patients’ independence in activities of daily living. Summative scores are used for this purpose, but this is problematic because the EADL is an ordinal level measurement scale.